Near infrared photothermal conversion materials: mechanism, preparation, and photothermal cancer therapy applications. Issue 38 (31st August 2021) - Li, Jie; Zhang, Wei; Ji, Wenhui; Wang, Jiqing; Wang, Nanxiang; Wu, Wanxia; Wu, Qiong; Hou, Xiyan; Hu, Wenbo; Li, Lin
Abstract : We outlined NIR photothermal materials for photothermal cancer therapy and proposed three key metrics for evaluating the materials from physical, chemical, and bio/medical perspectives. Abstract : Photothermal therapy (PTT) has been widely applied in cancer therapy as a result of its non-invasive, localized treatment and good therapeutic effect. In general, the final therapeutic effect of PTT mainly depends on the photothermal materials, which can be further considered to be determined by the photothermal conversion efficiency, biocompatibility, and photothermal stability of photothermal materials. In this review, photothermal materials including inorganic materials, organic materials, and organic–inorganic composite materials in recent years have been summarized in terms of the mechanism, preparation, and cancer therapy applications. In the end, the perspectives and obstacles in their further development are overviewed.